ANGKA BANDING APO B/APO A-I PADA GEJALA KORONER AKUT - Sienny Linawaty; JB. Suparyatmo; Tahono Tahono (Indonesian Association of Clinical Pathologist and Medical laboratory, 2013)
Coronary Artery Disease has a high prevalence and is frequently occurred and associated with the high mortality and morbidity. Dyslipidemia is one of the risk factors of Coronary Heart Disease (CHD). ApoB contained in very low-density lipoproteins (VLDL), intermediate-density lipoproteins (IDL), LDL and small dense LDL (sd-LDL), with one molecule of apoB in each particle. Apo A-I is the major apolipoprotein in HDL particles. The ratio of apoB/apoA-I is a balance between apoB-containing particles and potentially atherogenic apoA-I that is antiaterogenik. This study is carried to know the determination whether there are differences between apoB/ apoA-I ratio in patients dyslipidemia with ACS and non ACS. The research used a cross-sectional study design with patients dyslipidemia subjects suffering Acute Coronary Syndrome (ACS) and non ACS who enter to the Laboratory of Pathology Clinic at Dr. Moewardi Hospital between July and November 2011. To determine the pattern of data distribution, the researchers used Kolmogorov Smirnov test. For the analysis of differences in mean apoB/apoA-I ratio in the two population groups is used the T test, using a computer program, with the significance level p<0.05, 95% confidence interval. From 74 samples examined the mean age is 56.42 year old. This patients consisted of 33 males (44.6%) and 41 women (55.4%). All subjects are grouped into two groups, dyslipidemia ACS and non dyslipidemia ACS. The results showed apoB/apoA-I ratio significantly different in patients with dyslipidemia with ACS and non ACS. The mean apoB/apoA-I ratio of women and men subjects in both groups, including groups at high risk of myocardial myokard and higher than the cut-off ratio of apoB/ apoA-I (men 0.9 and women 0.8). It can be concluded that the apoB/apoA-I ratio of women and men subjects in both groups, included the high risk category for infarct myokard although lipid abnormalities are still not demonstrated to the risk of infarct myokard.